Általános iskolai és középiskolás diákok lemeztektonikai tévképzetei egy kvalitatív, keresztmetszeti vizsgálat tükrében - Kádár, Anett; Farsang, Andrea (Magyar Pedagógia, 2019)
Misconception research adds important knowledge to the research of conceptual change, which is the key process of learning and instruction. The study of misconceptions enables the analysis of the conceptual networks of both individuals and groups, and makes it possible to follow their changes over time. There has been a great amount of international research concerning geographical misconceptions, but it has been underrepresented in Hungary so far. Therefore, we decided to start unearthing how Hungarian students think about certain geographical concepts and phenomena. In the first step, we aimed at identifying plate-tectonics-related misconceptions in the framework of a cross-sectional, comparative analysis of five age groups (Ntotal=470). Convenience sampling was carried out in six primary and five secondary schools in 2012 and 2013. Employing data and methods triangulation, we collected multiple kinds of data by administering a three-part diagnostic test to students. The present study aims at introducing the misconceptions we found by using comparative content analysis. Our results indicate that Hungarian students are mainly characterized by preconceptions at a younger age, and by conceptual misconceptions at an older age. Vernacular misconceptions are present in a smaller proportion, while the proportions of cultural and popular misconceptions are insignificant. We argue that misconceptions should not be identified only as a problem, but also as an opportunity to help students develop a correct conceptual system in the course of teaching and learning. Furthermore, students should obtain transferable knowledge that can be used in their everyday life, their future work, and in other professional or scientific fields. However, if conceptual change does not happen, misconceptions may persist, or even intensify, and, as a result, they may later hinder meaningful learning and the development of proper critical thinking.